2019
DOI: 10.1101/742874
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

In silicoand empirical evaluation of twelve COI & 16S metabarcoding primer sets for insectivorous diet analyses

Abstract: This last decade, environmental DNA metabarcoding approaches have been developed and improved to minimize biological and technical biases; some challenges, however, remain, as the design of primers. Here we have performed a comprehensive assessment of ten COI and two 16S primer sets. We have combined in silico, in vivo-mock community of 33 arthropod taxa from 16 orders and guano analyses to identify primer sets that should maximize arthropod detection and taxonomic identification, whilst identifying bat specie… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 77 publications
0
7
0
Order By: Relevance
“…Although single pairs of primers may exhibit amplification biases for particular prey species (Clarke et al, 2014; Elbrecht et al, 2016, 2019), the ZBJ primers were specifically designed to amplify a large range of arthropods from the diet of European insectivorous bats (Zeale et al, 2011). Also, they are particularly well suited to recover lepidopterans and dipterans that represent the most consumed prey of long‐eared bats (Tournayre et al, 2020).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although single pairs of primers may exhibit amplification biases for particular prey species (Clarke et al, 2014; Elbrecht et al, 2016, 2019), the ZBJ primers were specifically designed to amplify a large range of arthropods from the diet of European insectivorous bats (Zeale et al, 2011). Also, they are particularly well suited to recover lepidopterans and dipterans that represent the most consumed prey of long‐eared bats (Tournayre et al, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…A 157 bp‐long fragment of the COI barcode gene was amplified using ZBJ primers (ZBJ‐ArtF1c and ZBJ‐ArtR2c) and a PCR setup detailed in Zeale et al (2011). The COI barcode is indeed currently the most efficient marker to get species‐level identifications of arthropods, as it covers the most extensive reference sequence database (Tournayre et al, 2020). Although single pairs of primers may exhibit amplification biases for particular prey species (Clarke et al, 2014; Elbrecht et al, 2016, 2019), the ZBJ primers were specifically designed to amplify a large range of arthropods from the diet of European insectivorous bats (Zeale et al, 2011).…”
Section: Methodsmentioning
confidence: 99%
“…It also offered the advantage of amplifying degraded DNA or rare DNA. In addition, Corse et al (2019) [33] and Tournayre et al (2019) [34] showed that primers used to amplify this mini-barcode were among the best over dozens of COI primer sets tested in silico. Several negative controls (n = 10) were included, according to recommendations made by Galan et al (2016) [35], such as: (i) negative controls for DNA extraction (NCext), (ii) negative controls for PCR (NCpcr), (iii) negative controls for indexing (NCindex: unused dual-index combinations), (iv) positive controls for PCR (PCpcr) and (v) positive controls for indexing (PCalien: DNA from beluga whale-Delphinapterus leucas-used to estimate the read misassignment frequency).…”
Section: Pcr and Illumina Sequencingmentioning
confidence: 99%
“…For arthropods, primers (MG-LCO1490 5 -ATTCHACDAAYCAYAARGAYATYGG-3 and MG-univ-R 5 -ACTATAAAARAAAYTATDAYAAADGCRTG-3 ) adapted by Galan et al (2018) [14] from the original primer sets designed by Gillet et al (2015) [32] were used. For vertebrate feces, primers (MG2-LCO1490 5 -TCHACHAAYCAYAARGAYATYGG-3 and MG2-univ-R 5 -ACYATRAARAARATYATDAYRAADGCRTG-3 ) adapted by Tournayre et al (2019) [34], were used (the bases in bold indicate the modifications to improve the primers). PCR reactions were carried out in a final volume of 10 µL containing 5 µL of Multiplex Master Mix (Qiagen, Hilden, Germany), 0.5 µM of each primer and 2 µL of DNA.…”
Section: Pcr and Illumina Sequencingmentioning
confidence: 99%
“…Dietary studies have also made use of non-invasive genetics such as the identification of invasive species through the diet of a carnivore (O'Meara et al 2014). Since the advent of DNA metabarcoding, the technique has been used to identify diverse prey groups such as those present in the bat diet (Russo et al 2018), and more recently, via non-invasively collected droppings from bat roosts (Tournayre et al 2019). However, in the case of Tournayre et al (2019), the authors relied on the DNA metabarcoding techniques and host amplification of the bat to identify the species of origin.…”
Section: Introductionmentioning
confidence: 99%